2011
DOI: 10.1007/s00299-011-1030-1
|View full text |Cite
|
Sign up to set email alerts
|

MpAsr encodes an intrinsically unstructured protein and enhances osmotic tolerance in transgenic Arabidopsis

Abstract: Abscisic acid-, stress- and ripening (ASR) -induced proteins are plant-specific proteins whose expression is up-regulated under abiotic stresses or during fruit ripening. In this study, we characterized an ASR protein from plantain to explore its physiological roles under osmotic stress. The expression pattern of MpAsr gene shows that MpAsr gene changed little at the mRNA level, while the MpASR protein accumulates under osmotic treatment. Through bioinformatic-based predictions, circular dichroism spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 56 publications
3
73
0
Order By: Relevance
“…40 Later studies revealed that Asr1-silenced tobacco plants showed increased glucose levels and lower Ht1 mRNA levels in source leaves 41 and that the heterologous over-expression of plantain ASR1 in Arabidopsis increased total soluble sugar levels in leaves. 26 In addition, Asr1 overexpression in maize plants increased yield and reduced sugar and amino acid levels; which suggests that ASR1 also participates in plant growth through the regulation of this kind of metabolites. 29 The Role of Asr1 in Sugar Metabolism Differs Among Species ASR1 functional analyses through the use of transgenic plants have shown that the metabolic effects depend not only on the species but also on the tissue under study.…”
Section: Functional Roles Of Asr1mentioning
confidence: 99%
See 2 more Smart Citations
“…40 Later studies revealed that Asr1-silenced tobacco plants showed increased glucose levels and lower Ht1 mRNA levels in source leaves 41 and that the heterologous over-expression of plantain ASR1 in Arabidopsis increased total soluble sugar levels in leaves. 26 In addition, Asr1 overexpression in maize plants increased yield and reduced sugar and amino acid levels; which suggests that ASR1 also participates in plant growth through the regulation of this kind of metabolites. 29 The Role of Asr1 in Sugar Metabolism Differs Among Species ASR1 functional analyses through the use of transgenic plants have shown that the metabolic effects depend not only on the species but also on the tissue under study.…”
Section: Functional Roles Of Asr1mentioning
confidence: 99%
“…Among others, this increase occurs in tobacco and tomato by osmotic and drought stress; 4,16,[20][21][22] in rice by drought, saline and osmotic stress; 10,23,24,25 and in plantain and banana by osmotic and biotic stress. 11,26,27 Only a few physiological studies with transgenic tomato, 28 tobacco, 22 maize, 29 and rice 18 plants have proved the involvement of ASR1 in stress tolerance.…”
Section: Functional Roles Of Asr1mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the ASR1 protein is present in the nucleus (Çakir et al, 2003;Wang et al, 2003;Kalifa et al, 2004a) and possesses a zinc-dependent DNA-binding activity (Kalifa et al, 2004a;Rom et al, 2006). In addition, fractionation assays and functional analyses suggest that the protein also localizes to the cytosol, where it has chaperone-like activity (Kalifa et al, 2004a;Konrad and Bar-Zvi, 2008;Urtasun et al, 2010;Dai et al, 2011;Hsu et al, 2011;Ricardi et al, 2012). Although the involvement of Asr genes in various abiotic and biotic stresses has been described (Amitai-Zeigersona et al, 1995;Jeanneau et al, 2002;Kalifa et al, 2004b;Yang et al, 2005;Liu et al, 2010;Dai et al, 2011;Henry et al, 2011;Hsu et al, 2011;Virlouvet et al, 2011;Jha et al, 2012;Arenhart et al, 2013), the exact molecular mechanism underlying their function remains unknown.…”
mentioning
confidence: 99%
“…It is possible that the lack of order in this domain contributes to functionality as seen in other eukaryotic proteins involved in cell signaling and transcription regulation. Disordered domains have been proposed to allow the transcription factor to fold in many ways, exposing different binding interfaces and thus giving them the ability to interact with multiple different partners [226][227][228][229] . Selective change of interaction partners may explain how ARF5 (and other activator ARFs) is involved in the regulation of multiple biological processes.…”
Section: Discussionmentioning
confidence: 99%